1980
DOI: 10.1111/j.1745-9125.1980.tb01309.x
|View full text |Cite
|
Sign up to set email alerts
|

Police Employment and Suburban Crime

Abstract: Although politicians, police, and others have often advocated the expansion of police employment in the effort to control crime, the empirical relationship between police employment and crime rates has seldom been systematically explored. This study incorporates variables which are causally related both to crime and police employment roles for the 252 northern and northeastern suburbs for which police employment and crime data are available for 1970–1972. Separate analyses of violent and property crime are und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 13 publications
1
21
0
2
Order By: Relevance
“…Finally, our findings revealed that the percentage of population that was African American was a highly significant predictor of police strength; it is clear that racial conflict theory contributed most strongly to the statistical model used to account for variation in police strength levels across U.S. cities. This finding is quite consistent with the existing literature on the continuing salience of racial inequity theories in U.S. society (Benson, Joong, Rasmussen, & Zuehlke, 1992;Chamlin, 1989;Huff & Stahura, 1980;Sever, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, our findings revealed that the percentage of population that was African American was a highly significant predictor of police strength; it is clear that racial conflict theory contributed most strongly to the statistical model used to account for variation in police strength levels across U.S. cities. This finding is quite consistent with the existing literature on the continuing salience of racial inequity theories in U.S. society (Benson, Joong, Rasmussen, & Zuehlke, 1992;Chamlin, 1989;Huff & Stahura, 1980;Sever, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…As per the routine activities model, motivated offenders and criminal opportunities are hypothesized to be positively related to arson rates. The effect of guardianship on crime rates is argued to be negative within the routine activities modeL There is, however, a literature that questions the existence and nature of this effect (e.g., Land and Felson 1976;Fox 1979;Huff and Stahura 1980). Most recently, Greenberg et aL (1983) found little evidence of a deterrent effect of police employment.…”
Section: Model Of Suburban Arson Ratesmentioning
confidence: 92%
“…Her study revealed that there was a significant positive correlation between percent black and the level of policing expenditures for the larger cities (i.e., at least 50,000 population), though not for cities with smaller populations. Huff and Stahura's (1980) study of suburbs in the North and Northeast disclosed that the racial composition of the suburb affected police employment. While a positive relationship existed between percent black and police employment, the primary impact of percent black on police employment was indirect through its positive relationship to another variable, percent lower class.…”
Section: Studies Examining Racial Compositionmentioning
confidence: 99%